Composite Nonlinear Feedback with Disturbance Observer for Active Front Steering - Sarah 'Atifah Saruchi; Hairi Zamzuri; Noraishikin Zulkarnain; Norbaiti Wahid; Mohd Hatta Mohammed Ariff (Institute of Advanced Engineering and Science, 2017)
One of the dominant virtue of Steer-By-Wire (SBW) vehicle is its capability to enhance handling performance by installing Active Front Steering (AFS) system without the driver’s interferences. Hence, this paper introduced an AFS control strategy using the combination of Composite Nonlinear Feedback (CNF) controller and Disturbance Observer (DOB) to achieve fast yaw rate tracking response which is also robust to the existence of disturbance. The proposed control strategy is simulated in J-curve and Lane change manoevres with the presence of side wind disturbance via Matlab/Simulink sotware. Futhermore, comparison with Proportional Integral Derivative (PID) and Linear Quadratic Regulator (LQR) controllers are also conducted to evaluate the effectiveness of the proposed controller. The results showed that the combined CNF and DOB strategy achieved the fastest yaw rate tracking capability with the least impact of disturbance in the AFS system installed in SBW vehicle.